MOTIVATION OF ENGLISH DEPARTMENT STUDENTS AT MUHAMMADIYAH UNIVERSITY OF NORTH MALUKU IN LEARNING ENGLISH THROUGH IMMERSION CAMP - Nurlaily Sofyan; Ummu Syahidah; Muhammad Yunus (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Ilmu Pendidikan Universitas Muhammadiyah Maluku Utara, 2021)
In learning English, each student has different motivations and motivation is the important key to get success in learning. The primary purpose of this research is to disclose the students’ motivation after joining the immersion camp. English Immersion Camp (EIC) is an English learning program where language learners are totally surrounded or immersed by the language they are learning. The research was conducted at English Department of Muhammadiyah University of North Maluku. The sample of this research was 20 English students who had participated in the English Immersion Camp for 3 days in Ternate City and 3 days in Tidore Island. Method use in this research was the combination of quantitative and qualitative method. The quantitative data of the questionnaire were analyzed in terms of means and percentages. For analyzing the qualitative part of the data, the interviewees’ responses for each question were transcribed. After that, the responses were analyzed in terms of themes related to the study objectives. The questionnaire consists of 10 questions in which question 1-5 are questions for intrinsic motivation and question 1-5 are questions for extrinsic motivation, while the interview data contains 5 questions. Data presented in the research findings it shows that the total average score of students' intrinsic motivation is 4,24 and student extrinsic motivation is 3,76 and this is a high ranking in the motivation level ranking. The result in this research also shows that students need an English learning program that can develop and improve their ability to communicate in English confidently and in the right way to motivate them in the process of learning English.